2020
DOI: 10.1111/trf.15917
|View full text |Cite
|
Sign up to set email alerts
|

The impact of blood product ratio and procoagulant therapy on the development of thromboembolic events in severely injured hemorrhaging trauma patients

Abstract: INTRODUCTION Transfusion therapy in hemorrhaging trauma patients is associated with the development of thromboembolic events. It is unknown whether current resuscitation strategies, including large volumes of plasma and early administration of procoagulant therapy, increases this risk. METHODS A systematic search was conducted in MEDLINE, PubMed, and Embase. Studies were screened by two independent reviewers and included if they reported on thromboembolic events in pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 56 publications
0
13
0
3
Order By: Relevance
“…Similarly, the ideal, fibrinogen dose and target level are not clear. Observational studies in trauma suggest a relation with low levels and mortality; conversely a possible association between higher fibrinogen levels and mortality [42] as well as with thrombosis [43]. More evidence is need regarding empirical and lab-based supplementation before a recommendation for or against early fibrinogen can be made; at the present time, either approach is justifiable on theoretical grounds.…”
Section: Justificationmentioning
confidence: 99%
“…Similarly, the ideal, fibrinogen dose and target level are not clear. Observational studies in trauma suggest a relation with low levels and mortality; conversely a possible association between higher fibrinogen levels and mortality [42] as well as with thrombosis [43]. More evidence is need regarding empirical and lab-based supplementation before a recommendation for or against early fibrinogen can be made; at the present time, either approach is justifiable on theoretical grounds.…”
Section: Justificationmentioning
confidence: 99%
“… 111 Studies show that the patients received tranexamic acid can significantly reduce the fibrinolytic activity and not increase the risk of VTE, even TEG, or other blood coagulation indexes within 24 h of admission shows the coming state of hypercoagulation status. 3 , 112 But a recent systemic review 113 indicated the use of tranexamic acid and fibrinogen concentrate was associated with the development of thromboembolic complications.…”
Section: Treatment and Prevention Of Trauma Vtementioning
confidence: 99%
“…Interessanterweise zeigte sich kein Unterschied in der Transfusionshäufigkeit zwischen der mit TXA und der ohne TXA behandelten Patientengruppe [ 45 ]. Trotz Kritik an methodischen Schwächen der Studie [ 4 , 38 ] sowie Hinweisen auf eine erhöhte Inzidenz von VTE in anderen Studien [ 22 , 37 , 57 ] etablierte sich die Dosierung von 1 g TXA als i.v.-Bolus und einer kontinuierlichen Gabe von 1 g i.v. über 8 h in verschiedenen Leitlinien und Empfehlungen [ 6 , 39 , 43 , 51 ] im Sinne einer frühen bzw.…”
Section: Tranexamsäure Bei Trauma Und Schädel-hirn-traumaunclassified